Methodological analysis of theories of the concept of nation - Abikenov, Zh.O. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This article provides a comprehensive overview of the main theoretical frameworks, taking a deeper look at theories related to the understanding of the issue of nationhood. Concepts and works of scientists who founded this concept were distinguished. Various perspectives on the formation of ethnic identity in modern society were explored. Because the nation is a complex and multifaceted structure that includes various disciplines and has attracted the attention of researchers. Any kind of understanding of the problem of the nation creates certain methodological difficulties during its research. It is important to compare the ways of understanding it and to identify the relevant points of view. The article analyzes the approaches of primordialism, constructivism and instrumentalism. And in the course of the discussion, theories that offer opposing views on ethnic identities will be discussed. Through this multidimensional analysis, the article attempts to provide a comprehensive account of the study of ethnic identity. Combining insights from various theoretical perspectives, it offers insights into the dynamic nature of ethnic identities and their relationship to social cohesion and cultural diversity in contemporary societies. The importance of combining different theories for a comprehensive understanding of the nation is emphasized and recommendations are made for developing an appreciation of cultural diversity.
Ұлт ұғымы теорияларын әдіснамалық талдау
Методологический анализ теорий понятия нации
Keywords: culture; tradition; innovation; society; science; research; method; refinement; education; value